2003
DOI: 10.1002/jmv.10395
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to the nonglycosylated ectodomain of respiratory syncytial virus attachment glycoprotein mediate pulmonary eosinophilia in inbred strains of mice with different MHC haplotypes

Abstract: Development of subunit vaccines against respiratory syncytial virus (RSV) for naive human infants is hindered by concerns that immunization with the fusion or attachment (G) proteins will elicit polarized Type 2 T cell responses and cause immunopotentiation upon subsequent natural infection. We investigated the regions of G protein responsible for inducing a Type 2 T cell phenotype in inbred mice of different MHC haplotype toward development of vaccines with improved safety. As demonstrated by IL-5-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
3
17
0
2
Order By: Relevance
“…Alternatively, secondary epitopes outside the central ectodomain may yield type 2 T-cell responses against G protein that result in eosinophilia. Previous studies (24,48,55) …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Alternatively, secondary epitopes outside the central ectodomain may yield type 2 T-cell responses against G protein that result in eosinophilia. Previous studies (24,48,55) …”
Section: Discussionmentioning
confidence: 94%
“…Our strategy was based on results from studies that indicated that PBMC from most adult human donors were readily activated upon stimulation with peptide antigens from the region of G protein spanned by amino acids 149 to 200 (20). It was further demonstrated that epitopes within the region primed several inbred strains of mice for pulmonary eosinophilia (24). At first, it was not clear what impact genetic alteration of this magnitude would have on attenuation, immunogenicity, and pulmonary eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary eosinophilia also occurs after RSV challenge of BALB/c mice previously immunized with a recombinant vaccinia virus (vacv) expressing the attachment (G) protein of RSV (vacvG) [32][33][34][35][36]. Similar to the memory T cell response induced following FI-RSV immunization, the memory T cell response to the G protein consists of CD4 but not CD8 T cells [37][38][39].…”
Section: The Contribution Of Memory Cd4 T Cells To Rsv Vaccine-enhancmentioning
confidence: 99%